Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the given equation [tex]\(\log_4 x + \log_4 (x + 6) = 2\)[/tex], let's follow the steps:
1. Understand the logarithmic properties:
Recall the property of logarithms that states [tex]\(\log_b(m) + \log_b(n) = \log_b(m \cdot n)\)[/tex].
2. Combine the logarithms:
Using the property, we can combine the logarithms on the left-hand side:
[tex]\[ \log_4 x + \log_4 (x + 6) = \log_4 [x(x + 6)] \][/tex]
3. Substitute and simplify:
Substitute the combined logarithm back into the equation:
[tex]\[ \log_4 [x(x + 6)] = 2 \][/tex]
4. Exponentiate to remove the logarithm:
To isolate [tex]\(x\)[/tex], rewrite the equation in exponential form:
[tex]\[ x(x + 6) = 4^2 \][/tex]
[tex]\[ x(x + 6) = 16 \][/tex]
5. Solve the quadratic equation:
The equation [tex]\(x(x + 6) = 16\)[/tex] simplifies to:
[tex]\[ x^2 + 6x - 16 = 0 \][/tex]
To solve this quadratic equation, we use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 6\)[/tex], and [tex]\(c = -16\)[/tex].
6. Apply the quadratic formula:
[tex]\[ x = \frac{-6 \pm \sqrt{6^2 - 4 \cdot 1 \cdot (-16)}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{36 + 64}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{100}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm 10}{2} \][/tex]
7. Calculate the solutions:
This gives us two potential solutions:
[tex]\[ x = \frac{-6 + 10}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ x = \frac{-6 - 10}{2} = \frac{-16}{2} = -8 \][/tex]
8. Check the validity of the solutions:
Since logarithms are only defined for positive real numbers in this context, we must ensure that both [tex]\(x\)[/tex] and [tex]\(x+6\)[/tex] are positive:
- For [tex]\(x = 2\)[/tex]: [tex]\(\log_4 2\)[/tex] and [tex]\(\log_4 8\)[/tex] are valid.
- For [tex]\(x = -8\)[/tex]: [tex]\(\log_4 (-8)\)[/tex] is not valid as logarithms of negative numbers are undefined in the real number system.
Thus, the only valid solution is:
[tex]\[ x = 2 \][/tex]
Therefore, the potential solution among the given choices is:
[tex]\[ x = 2 \][/tex]
1. Understand the logarithmic properties:
Recall the property of logarithms that states [tex]\(\log_b(m) + \log_b(n) = \log_b(m \cdot n)\)[/tex].
2. Combine the logarithms:
Using the property, we can combine the logarithms on the left-hand side:
[tex]\[ \log_4 x + \log_4 (x + 6) = \log_4 [x(x + 6)] \][/tex]
3. Substitute and simplify:
Substitute the combined logarithm back into the equation:
[tex]\[ \log_4 [x(x + 6)] = 2 \][/tex]
4. Exponentiate to remove the logarithm:
To isolate [tex]\(x\)[/tex], rewrite the equation in exponential form:
[tex]\[ x(x + 6) = 4^2 \][/tex]
[tex]\[ x(x + 6) = 16 \][/tex]
5. Solve the quadratic equation:
The equation [tex]\(x(x + 6) = 16\)[/tex] simplifies to:
[tex]\[ x^2 + 6x - 16 = 0 \][/tex]
To solve this quadratic equation, we use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = 6\)[/tex], and [tex]\(c = -16\)[/tex].
6. Apply the quadratic formula:
[tex]\[ x = \frac{-6 \pm \sqrt{6^2 - 4 \cdot 1 \cdot (-16)}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{36 + 64}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm \sqrt{100}}{2} \][/tex]
[tex]\[ x = \frac{-6 \pm 10}{2} \][/tex]
7. Calculate the solutions:
This gives us two potential solutions:
[tex]\[ x = \frac{-6 + 10}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ x = \frac{-6 - 10}{2} = \frac{-16}{2} = -8 \][/tex]
8. Check the validity of the solutions:
Since logarithms are only defined for positive real numbers in this context, we must ensure that both [tex]\(x\)[/tex] and [tex]\(x+6\)[/tex] are positive:
- For [tex]\(x = 2\)[/tex]: [tex]\(\log_4 2\)[/tex] and [tex]\(\log_4 8\)[/tex] are valid.
- For [tex]\(x = -8\)[/tex]: [tex]\(\log_4 (-8)\)[/tex] is not valid as logarithms of negative numbers are undefined in the real number system.
Thus, the only valid solution is:
[tex]\[ x = 2 \][/tex]
Therefore, the potential solution among the given choices is:
[tex]\[ x = 2 \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.